Chroma key photography and the tricks of cinematographic bedazzlement - سهيلة دهماني; إيمان لمين (International Journal of Social Communication, 2025)
Since the dawn of film-making, visual dazzling is the sole worry and obsession of this arts experts because it’s considered to be one of the most important means to attract the minds of audiences and one of the elements of visual dazzling making is the chroma-key photography. It is a technique that uses a green and blue colored background while filming cinematographic or TV scenes. This technique has become crucial to a point that it decreased the costs of filming locations and created huge and spectaculars sets which have served immensely the dramatic build-up in cinematographic films. For this reason, the article introduces the chroma technique and the beginnings of its use and the most important international movies that has dazzled audiences